Addressing Morbid Obesity as a Barrier to Renal Transplantation With Laparoscopic Sleeve Gastrectomy. Issue 5 (23rd February 2015) - Freeman, C. M.; Woodle, E. S.; Shi, J.; Alexander, J. W.; Leggett, P. L.; Shah, S. A.; Paterno, F.; Cuffy, M. C.; Govil, A.; Mogilishetty, G.; Alloway, R. R.; Hanseman, D.; et al.
Abstract: Morbid obesity is a barrier to renal transplantation and is inadequately addressed by medical therapy. We present results of a prospective evaluation of laparoscopic sleeve gastrectomy (LSG) for patients failing to achieve significant weight loss with medical therapy. Over a 25‐month period, 52 obese renal transplant candidates meeting NIH guidelines for metabolic surgery underwent LSG. Mean age was 50.0 ± 10.0 years with an average preoperative BMI of 43.0 ± 5.4 kg/m 2 (range 35.8–67.7 kg/m 2 ). Follow‐up after LSG was 220 ± 152 days (range 26–733 days) with last BMI of 36.3 ± 5.3 kg/m 2 (range 29.2–49.8 kg/m 2 ) with 29 (55.8%) patients achieving goal BMI of <35 kg/m 2 at 92 ± 92 days (range 13–420 days). The mean percentage of excess weight loss (%EWL) was 32.1 ± 17.6% (range 6.7–93.8%). A segmented regression model was used to compare medical therapy versus LSG. This revealed a statistically significant increase in the BMI reduction rate (0.3 kg/m 2 /month versus 1.1 kg/m 2 /month, p < 0.0001). Patients also experienced a 40.9% decrease in anti‐hypertensive medications (p < 0.001) and a 49.7% decrease in total daily insulin dose (p < 0.001). LSG is a safe and effective means for addressing obesity in kidney transplant candidates in the context of a multidisciplinary approach. Abstract : The use of laparoscopic sleeve gastrectomy in morbidly obese end‐stage renal disease patients may be a safe and effective means of improving access to transplantation, with marked increases in rate of weight loss compared to medical weight‐loss regimens, and overall low mortality and morbidity rates comparable to those previously reported in the general population.